PENGARUH FEE AUDIT, INDEPENDENSI DAN UKURAN KAP TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI WILAYAH JAKARTA SELATAN - Nathania Jennifer Stanley; Leonard Pangaribuan (Jurnal Akuntansi, 2023)
Audit quality is all possibilities where when auditing the client's financial statements can find violations that occur in the client's accounting system. An auditor is required to produce high quality and good work, because the auditor has a great responsibility to various parties with an interest in the financial statements of a company, including the public. This study aims to provide empirical evidence of the effect of audit fees, independence and KAP size on audit quality. Based on the Public Accountant Professional Standards (SPAP) the audit carried out by the auditor is said to be of good quality, if it meets general standards, fieldwork standards and reporting standards. Data analysis methods in this study consisted of descriptive statistical analysis, data quality testing, classical assumption testing, and hypothesis testing. After conducting the test, the research results obtained from the t statistical test for audit fees which have a significance value of 0.031 (<0.05), independence has a significance value of 0.0005 (<0.05) and KAP size with a significance value of 0.3455 (>0.05). Based on these results, the researcher draws the conclusion that audit fees have a negative effect on audit quality, independence has a positive effect on audit quality and KAP size has no effect on audit quality.